Sustainable Nutrient Management for NFT Hydroponic Lettuce: Integrating Kipahit (Tithonia diversifolia) Liquid Organic Fertilizer with AB-Mix - Linh, Ta Thi Thuy; Thammachot, Nasaporn (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to determine the optimal combination of kipahit liquid organic fertilizer concentration and AB Mix to enhance the growth and production of green lettuce using the nutrient film technique in hydroponics. Methodology: This study used a completely randomized design with 5 treatments, namely P1 = liquid organic fertilizer kipahit 0% + AB Mix 100% (control), P2 = liquid organic fertilizer kipahit 25%+AB Mix 75%, P3 = liquid organic fertilizer kipahit 50%+AB Mix 50%, P4= liquid organic fertilizer kipahit 75%+AB Mix 25%, P5=POC kipahit 100% + AB Mix 0%. Data analysis used the test of variance (ANOVA) and the DMRT follow-up test at the 5% level. Main Findings: The provision of AB Mix and liquid organic fertilizer Kipahit nutrition had a significant effect on all parameters. P2 is a combination treatment of AB Mix and liquid organic fertilizer Kipahit, which can reduce the use of AB Mix nutrients on the parameters of plant height, leaf length, leaf width, number of leaves, and plant wet weight, but cannot increase plant growth and production of green lettuce compared to the use of 100% AB Mix. No combination of kipahit liquid organic fertilizer concentration and Ab Mix could increase the growth and production of green lettuce compared to using 100% AB Mix. Novelty/Originality of this study: This study provides new insights into the potential of kipahit liquid organic fertilizer as a partial substitute for AB Mix in NFT hydroponics for lettuce production.